1989
DOI: 10.1109/32.24721
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Charlotte: simplicity and function in a distributed operating system

Abstract: This paper presents a retrospective view of the Charlotte distributed operating system, a testbed for developing techniques and tools to solve computation-intensive problems with large-grain parallelism. The final version of Charlotte runs on the Crystal multicomputer, a collection of VAX-111750 computers connected by a local-area network. The kernellprocess interface is unique in its support for symmetric, bidirectional communication paths (called links), and synchronous nonblocking communication. Our experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…2 For the definition and a description of implementations of distributed operating systems see e.g. Tanenbaum, van Renesse (1985), Cheriton (1988) or Finkel et al (1989).…”
Section: Process Migration In Distributed Computing Systemsmentioning
confidence: 99%
“…2 For the definition and a description of implementations of distributed operating systems see e.g. Tanenbaum, van Renesse (1985), Cheriton (1988) or Finkel et al (1989).…”
Section: Process Migration In Distributed Computing Systemsmentioning
confidence: 99%
“…the vertical organization is likely to perform better on a machine with uniform memory [7]. 1be horizontal crganizatlon may be easier to debug [10]. Most Unix kernels are vertical Demos [4] and Minix [21] are horizontal.…”
Section: Compatibility With the Conceptual Model Orkernel Organizationmentioning
confidence: 99%
“…Motivation for Lynx grew out of experience with the Charlotte distributed operating system [2,12]. Like many other systems developed in the 1970's and early 1980's, Charlotte was designed to provide many of its services in user-level processes, rather than in the kernel.…”
Section: Motivationmentioning
confidence: 99%
“…Motivation for Lynx is discussed in section 2. Lynx was developed at the University of Wisconsin, where it was first implemented on the Charlotte multicomputer operating system [2,12]. Charlotte was designed without Lynx, but experience with a conventional library interface to the kernel suggested that language support for communication could make the programmer's life much easier.…”
Section: Introductionmentioning
confidence: 99%